Lonely older adults are more likely to delay or avoid medical care during the coronavirus disease 2019 pandemic. (16th February 2022) - Li, Yue; Cheng, Zijing; Cai, Xueya; Holloway, Melissa; Maeng, Daniel; Simning, Adam
Abstract: Objectives: To examine the relationship between loneliness and self‐reported delay or avoidance of medical care among community‐dwelling older adults during the coronavirus disease 2019 (COVID‐19) pandemic. Methods: Analyses of data from a nationally representative survey administered in June of 2020, in COVID‐19 module of the Health and Retirement Study. Bivariate and multivariable analyses determined associations of loneliness with the likelihood of, reasons for, and types of care delay or avoidance. Results: The rate of care delay or avoidance since March of 2020 was 29.1% among all respondents (n = 1997), and 10.1% higher for lonely (n = 1, 150%, 57.6%) versus non‐lonely respondents (33.5% vs. 23.4%; odds ratio = 1.59, p  = 0.003 after covariate adjustment). The differences were considerably larger among several subgroups such as those with emotional/psychiatric problems. Lonely older adults were more likely to cite "Decided it could wait, " "Was afraid to go, " and "Couldn't afford it" as reasons for delayed or avoided care. Both groups reported dental care and doctor's visit as the two most common care delayed or avoided. Conclusions: Loneliness is associated with a higher likelihood of delaying or avoiding medical care among older adults during the pandemic. Key points: What is the primary question addressed by this study? What is the relationship between loneliness and self‐reported delay or avoidance of medical care among community‐dwelling older adults during the coronavirus disease 2019 (COVID‐19) pandemic? What is the main finding of this study? Loneliness predicts a higher likelihood of delaying or avoiding medical care during the COVID‐19 pandemic among older adults. This association is stronger among several high‐risk groups such as those with emotional/psychiatric problems. What is the meaning of the finding? Interventions to address loneliness among older adults have the potential to reduce unmet care needs and adverse health outcomes.